The critical period for brown adipocyte development: Genetic and environmental influences - Chabowska‐Kita, Agnieszka (Obesity (Silver Spring), 2016)
OBJECTIVE: The current review summarizes recent advances in the origin of brown adipocytes in rodents and humans. METHODS: This review describes recent insights into induction of the brown adipocyte phenotype (BAP) in white fat (WAT) revealed by murine studies during the early postnatal period and reversible temperature transitions. The origin of adipocytes and identity of progenitors as indicated by lineage tracing experiments are reviewed. RESULTS: We describe a genetic model for brown adipocyte development that involves the appearance of brown adipocytes in WAT at 21 days of age and a mechanism of post‐weaning involution relevant for acquisition of the BAP in fully functional WAT in mice. Under normal physiological conditions, the BAP is dormant with the potential to be stimulated by changes in the external environment. Current evidence for the acquisition of brown adipocytes by interconversion of mature adipocytes versus de novo recruitment of progenitors suggests that mechanisms for acquisition of the BAP in WAT in mice are depot‐specific and controlled by allelic variation. CONCLUSIONS: Although the BAP is highly variable among mice, there is no information on genetic variability in the expression of brown adipocytes in humans. Thus, deeper understanding of genetic mechanisms underlying development of functional brown adipocytes is crucial.